Bimbingan Belajar Matematika Bagi Anak Panti Asuhan di Bandung Raya - Yayu L.S. (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
The Taman Harapan and Puteri Sartika are two orphanages that provide services to orphaned children. The orphans, are children who have complete parents but being neglected, and children living in households who experience psychological disorders. Mathematics achievement problems are still arguably a concern, not the only problem in both homes (The Taman Harapan and Puteri Sartika), yet the problem should be reduced or even eliminated. There are many ways can be done, starting from the provision of tutoring, and trainings to improve motivation. Tutoring is done once a week. Before implementing tutoring, it is given a pretest to measure students’ learning outcomes from both homes. Thereafter, the post-test held to measure students' final learning outcomes. Meanwhile, to increase students’ motivation, training (motivation) is given by first providing initial questionnaire to measure the initial motivation and final questionnaire to measure motivation subsequent to the given training. The results obtained after training and motivation tutoring is the escalation of mathematics achievement and students’motivation in both homes